Optimizing Grain Filling And Nitrogenuse Efficiency Of Irrigated Rice (Oryza Sativa L.) Through Timely Nitrogen Application During Reproductive Growth Stage - Bah, Alagie (2009)

(untitled)
In the tropics, Nitrogen is considered an indispensible source of nutritional element for the productivity of most crops, especially paddy rice (Oryza sativa L.). In flooded rice, applied N fertilizer may be susceptible to losses when the time of application does not match with period of crop demand. Knowledge about accurate timing of N during the reproductive growth stage of flooded rice may be useful in optimizing nitrogen recovery efficiency. A glasshouse experiment was conducted to determine the critical time of nitrogen fertilizer application during panicle initiation (PI) stage to optimize nitrogen recovery efficiency, grain filling and yield of two Malaysian rice cultivars (MR219 and MR232). The treatments comprised a control without N applied (N1) and different timings of urea N-fertilizer applied at the rate of 60 kg N ha-1 during panicle initiation stage at 45 (N2), 50 (N3), 55 (N4), 60 (N5) and 65 (N6) days after seeding (DAS) with five replications. The results indicated that plant physiological parameters showed statistical difference among some treatments.Chlorophyll meter reading (Minolta SPAD-502 leaf chlorophyll meter) for cultivar MR219 in treatment receiving 60 kg N ha-1 at 55 days after seeding, gave the highest reading and was significantly higher (P ≤ 0.05) compared with treatments receiving 60 kg N ha-1 at 60, 65 days after seeding and control, where as for MR232, chlorophyll content for treatment receiving 60 kg N ha-1 at 55 days after seeding was significantly higher in contrast to treatment receiving 60 kg N ha-1 at 45, 60, 65 days after seeding and the control. In cultivar MR219, treatment receiving 60 kg N ha-1 at 55 days after seeding produced the highest plant height (92.2 cm) compared to control (77.4 cm) and treatments receiving 60 kg N ha-1 at 45 (85.6 cm) and 65 (84.2 cm) days after seeding, while for cultivar MR232, treatments receiving 60 kg N ha-1 at 50 days after seeding recorded the highest height (96.0 cm). Higher leaf area index (LAI) was observed in treatments receiving 60 kg N ha-1 at 50 and 55 days after seeding for both cultivars. Application of N also resulted in an increased in plant biomass, and was found to be higher in treatment receiving 60 kg N ha-1 at 55 days after seeding (400.2 g pot-1) for cultivar MR219, while for MR232, significant increased was observed in treatment receiving 60 kg N ha-1 at 50 (367.2 g pot-1). Plant yield and yield component parameters were significantly influenced by timing of N applied during the reproductive stage. Percentage of productive tillers for both cultivars did not significantly vary among treatments except with control. The spikelet number panicle-1 was higher in treatments receiving 60 kg N ha-1 at 50 and 55 days after seeding for both cultivars. The highest 1000-grain weight (30.3 g) and filled grain percentage (94 %) were recorded in treatments fertilized with N at 55 DAS (N4) for cultivar MR219, while for MR232, similar trend was also obtained with the same treatment (N4), recording the highest 1000-grain weight (28.6 g) and filled grain percentage (89%). Rice grain yield in cultivar MR219 was significantly higher with treatment receiving 60 kg N ha-1 at 55 days after seeding (225.75 g pot-1) and treatments receiving 60 kg N ha-1 at 50 and 55 days after seeding for MR232 (210.57 and 214.61g pot-1, respectively). The extent of decrease in grain yield due to late N fertilization during reproductive stage in treatments receiving 60 kg N ha-1 at 65 days after seeding for cultivars MR219 and MR232 were 39% and 17%, respectively. Based on grain yield, cultivar MR219 tend to be more sensitive to timing of N fertilizer than MR232 N uptake in rice significantly varies with timing of N fertilizer. In both MR219 and MR232, higher Nitrogen recovery efficiency was obtained in treatments receiving 60 kg N ha-1 at 55 days after seeding (77% and 72%, respectively).